The Responsibility of A Notary Regarding The Cancellation of a Notarial Deed Containing a Pretended Agreement Based on a Decision From the District Court - Fitrotinisak, Istna Kamelina; Huda, Mokhamad Khoirul (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
There are various ways a person can obtain land rights, including borrowing and borrowing by handing over land rights as collateral. The lending party also makes a power of sale agreement and follows up on the sale and purchase agreement. When the borrower breaks the contract, the lending party approaches the PPAT to have a sale and purchase deed drawn up and registered with the Land Office for name change purposes. The method used is normative juridical with a statutory regulation approach, concept approach and case approach. The research results obtained: The land sale agreement made before the PPAT is not the same as in fact it does not have legal force, does not meet objective requirements, so the result is that it is null and void/is considered non-existent. PPATs that make pseudo-agreements do not apply the precautionary principle in making deeds, namely acting untrustworthy, dishonest, not thorough, not independent, taking sides, and not safeguarding the interests of the parties involved in legal actions. The notary's actions violate the Debtor's rights which are protected by law. Debtors can sue for compensation on the basis of violating Article 1365 of the Civil Code in conjunction with Article 16 paragraph (12) UUJN, violating Article 3 point 4 of the Notary Code of Ethics.